P-Se divacancy MoP / MoSe2 heterojunction materials and their applications

By constructing P-Se double-vacancies MoP/MoSe2 heterojunction material, the problem of unsatisfactory catalytic performance of existing HER catalytic materials is solved, and the excellent HER catalytic performance under acid and alkali systems and the effect of excellent hydrogen production and electricity production capabilities are achieved.

CN116532138BActive Publication Date: 2025-04-11JIAXING DAZE PHOTOENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202211639026.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-04-11
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

The catalytic performance of existing HER catalytic materials is not ideal, and there is a lack of functional materials that take into account both excellent hydrogen production and electricity production properties.

Method used

Using P-Se double vacancy MoP/MoSe2 heterojunction material, a double vacancy heterojunction structure was constructed by preforming MoSe2 nanosheets and phosphating on their surfaces, combined with calcination treatment under a negative pressure-reduction atmosphere.

Benefits of technology

It exhibits excellent HER catalytic performance under acid and alkali systems, taking into account excellent hydrogen production and electricity production capabilities, and even surpasses commercial Pt/C at high current density in alkaline media.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116532138B_ABST
    Figure CN116532138B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of HER materials, and specifically relates to a P-Se divacancy MoP / MoSe2 heterojunction material, comprising a MoSe2 nanosheet with Se vacancies and a MoP nanosheet with P vacancies composited on the surface thereof, and the composite interface of the two has a heterojunction structure. The present invention also includes a preparation method and application of the material. The material of the present invention has excellent HER performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of catalytic materials, and in particular to the field of HER catalytic materials. Background Art

[0002] In recent decades, due to the massive consumption of fossil fuels, energy shortages and environmental pollution, clean energy (such as hydrogen energy) has received extensive attention. As the first step in the utilization of hydrogen energy, electrocatalytic water splitting has been considered a promising hydrogen production technology due to its high economic benefits, high efficiency and green cleanliness. The hydrogen evolution reaction (HER) as a half-reaction of water splitting has been widely studied, and the corresponding electrocatalysts have also been rapidly developed. So far, Pt / C is the most advanced electrocatalyst, but its high cost and scarcity have severely limited its industrial application. Therefore, it is crucial to research and develop low-cost non-precious metal catalysts with high HER catalytic activity, such as two-dimensional transition metal chalcogenides (TMDs), two-dimensional transition metal phosphides (TMPs), and two-dimensional transition metal nitrides (TMNs). Two-dimensional materials have high specific surface area, a large number of unsaturated coordinated atoms, unique morphology and structure, and adjustable electronic structure. For example, MoS 2 Se and S have similar chemical properties, and MoSe 2 With MoS 2 The same layered nanostructure makes MoSe 2 However, so far, MoSe 2 Therefore, it is urgent to develop some effective strategies to further improve the HER performance of MoSe. 2 In addition, although the designed HER electrocatalyst has reduced the overpotential as much as possible, the amount of electricity consumed for large-scale hydrogen production is still very large. The industry still lacks functional materials that have both excellent hydrogen production and synchronous electricity production performance. Summary of the invention

[0003] In view of the problem that the catalytic performance of existing HER catalytic materials is not ideal, the first object of the present invention is to provide a P-Se divacancy MoP / MoSe 2 Heterojunction materials aim to provide a new material that can exhibit excellent HER catalytic performance in both acid and alkaline systems and can achieve both excellent hydrogen production and power generation performance.

[0004] The second object of the present invention is to provide the P-Se divacancy MoP / MoSe 2 The method for preparing heterojunction materials aims to prepare new materials with the above-mentioned special structural characteristics and excellent hydrogen and electricity production performance.

[0005] The third object of the present invention is to provide the P-Se divacancy MoP / MoSe 2 Application of heterojunction materials as HER catalysts.

[0006] The fourth object of the present invention is to provide a MoP / MoSe containing the P-Se divacancy 2 Electrodes of heterojunction materials.

[0007] The fifth object of the present invention is to provide a MoP / MoSe comprising the P-Se divacancy 2 Heterojunction material water electrolysis hydrogen production device and battery.

[0008] A P-Se divacancy MoP / MoSe 2 Heterojunction materials, including MoSe with Se vacancies 2 The nanosheet and the MoP nanosheet with P vacancies composited on the surface of the nanosheet, and the composite interface of the two has a heterojunction structure.

[0009] The present invention provides a MoP / MoSe heterojunction structure having a P-Se double vacancy 2 Composite two-dimensional materials. The study found that this special P-Se double vacancy and MoP / MoSe 2 Materials with heterojunction structures have abundant electroactive sites and fast charge transfer capabilities. They exhibit low overpotentials in both alkaline and acidic media, and can even surpass commercial Pt / C at high current densities in alkaline media. They can exhibit excellent HER catalytic activity. In addition, they also have excellent hydrogen and electricity production capabilities.

[0010] Preferably, the P-Se divacancy MoP / MoSe 2 Heterojunction material, having a flower-like nanosheet structure. The material of the structure of the present invention, combined with the P-Se double vacancy and MoP / MoSe 2 The heterojunction results can further synergistically improve the HER performance.

[0011] The present invention also provides the P-Se divacancy MoP / MoSe 2 Preparation method of heterojunction material, preparation of MoSe 2 Nanosheets are then surface phosphated in a phosphorus-containing atmosphere to obtain MoP / MoSe 2 Heterojunction materials; among them, P and MoSe in the phosphorus source 2 The molar ratio of the nanosheets is 300 to 500:1, and the phosphating temperature is 700 to 900°C;

[0012] MoP / MoSe2 The heterojunction material is calcined under a reducing atmosphere and negative pressure to obtain the P-Se divacancy MoP / MoSe 2 Heterojunction material; wherein the calcination temperature is 700-900°C.

[0013] The preparation of the new material described in the present invention needs to overcome the difficulties in the preparation of heterojunction structure and the difficulty in forming and controlling P-Se double vacancies. In addition, it also faces the problem of unsatisfactory hydrogen and power generation performance of the prepared material. In view of the preparation difficulties of the new material, the present invention has found through research that the MoSe 2 Nanosheets, combined with surface phosphating, calcination activation under negative pressure-reducing atmosphere and treatment parameters such as the ratio of the phosphating stage, temperature, calcination negative pressure and temperature, can synergistically construct the new material of the double vacancy heterojunction structure, which helps to improve the physical and chemical properties of the material, and then can synergistically improve the HER performance of the material and improve its hydrogen and electricity production capabilities.

[0014] In the present invention, the MoSe 2 Nanosheets can be prepared based on existing methods.

[0015] Preferably, a molybdenum source and a selenium source are subjected to a hydrothermal reaction to obtain the MoSe 2 Nanosheets.

[0016] Preferably, the modified carbon cloth, molybdenum source and selenium source are subjected to hydrothermal reaction to obtain the flower-shaped MoSe 2 Nanosheets;

[0017] Preferably, the modified carbon cloth is a nitrated carbon cloth;

[0018] Preferably, the molybdenum source is at least one of molybdates including ammonium molybdate;

[0019] Preferably, the selenium source is at least one of elemental selenium and selenate;

[0020] Preferably, the temperature of the hydrothermal reaction is 150 to 250°C, preferably 180 to 220°C, and more preferably 190 to 210°C.

[0021] In the present invention, in order to facilitate the subsequent preparation, MoSe 2 The nanosheets are grown on a flat support.

[0022] In the present invention, it is preferred to adopt a gas phase surface reaction method to form a MoSe 2 The surface of the nanosheet is phosphated to form the MoP / MoSe 2 Heterojunction materials.

[0023] In the present invention, the phosphorus source is PH 3 Or it can be converted into PH 3 Precursors of

[0024] Preferably, the precursor is at least one of sodium hypophosphite, potassium hypophosphite, red phosphorus, etc.;

[0025] Preferably, in the surface phosphating stage, the precursor is placed upstream of the gas source to 2 Downstream of the nanosheet gas source, the phosphorus source is heated and volatilized under the carrier gas, and the MoSe 2 The surface of the nanosheets was phosphated;

[0026] In the present invention, the surface phosphating process is further coordinated with the combined control of the P source ratio, the atmosphere flow rate and the temperature, which helps to further facilitate the preparation of the material of the structure.

[0027] Preferably, the temperature of the phosphating stage is 750-850°C;

[0028] Preferably, the carrier gas is at least one of nitrogen and an inert gas;

[0029] Preferably, the flow rate of the carrier gas in the phosphating stage is less than or equal to 50 mL / min, more preferably 10 to 30 mL / min, and most preferably 15 to 25 mL / min;

[0030] Preferably, the phosphating time is 0.5 to 1.5 hours.

[0031] In the present invention, the heterojunction material is innovatively calcined under negative pressure and reducing atmosphere, and further coordinated with the joint control of the calcination temperature, which helps to synergistically construct surface P-Se divacancies, reduce structural etching, and help regulate the microstructure, thereby further improving the HER performance of the material and improving its hydrogen and electricity production performance.

[0032] In the present invention, during the calcination process, the reducing atmosphere is a hydrogen-containing atmosphere;

[0033] Preferably, the reducing atmosphere is at least one of hydrogen, a hydrogen-nitrogen mixture, and a hydrogen-inert gas mixture;

[0034] Preferably, the volume content of hydrogen in the reducing atmosphere is greater than or equal to 1% by volume, preferably 10 to 100% by volume; considering the processing cost and preparation value, 5 to 15% is further preferred;

[0035] Preferably, the negative pressure during the roasting stage is less than or equal to 250 Pa;

[0036] Preferably, the calcination temperature is 750-850° C. In the present invention, at this preferred temperature, it is helpful to further synergistically improve the HER performance of the prepared material.

[0037] In the present invention, there is no particular requirement for the rate of heating to the calcination temperature, which may be, for example, 1 to 20° C. / min, preferably 5 to 15° C. / min.

[0038] Preferably, the holding time at the roasting temperature is 0.5 to 5 hours, and more preferably 1 to 2 hours.

[0039] The present invention also provides a P-Se divacancy MoP / MoSe 2 Application of heterojunction materials as HER catalysts.

[0040] In the present invention, the P-Se divacancy MoP / MoSe can be prepared based on existing methods. 2 Heterojunction materials are used to prepare HER catalytic devices. For example, they are used as HER catalysts to prepare hydrogen production from water electrolysis and Zn-H 2 O battery, more preferably a diaphragm-free Zn-H 2 OBattery.

[0041] The present invention also provides a HER catalytic electrode, which comprises the P-Se divacancy MoP / MoSe 2 Heterojunction materials.

[0042] In the present invention, the HER catalytic electrode is added with the P-Se divacancy MoP / MoSe 2 The active materials of the heterojunction material, other auxiliary materials and structural components may all be known.

[0043] The present invention also provides a device (or device) containing the HER catalytic electrode, which can be a water electrolysis hydrogen production device or a zinc water battery. Similarly, the device of the present invention contains the P-Se divacancy MoP / MoSe 2 Except for the active material of the heterojunction material, other materials and structures may be known.

[0044] The Zn-H 2 The half reaction of the O cell is Zn+2OH - -2e - →ZnO+H 2 O. The device can reduce the demand for electrical energy by harvesting chemical energy. Thanks to the new material described in the present invention, it can achieve the simultaneous production of hydrogen and electricity.

[0045] Beneficial Effects

[0046] 1. The present invention provides a new P-Se divacancy MoP / MoSe 2 Heterojunction materials exhibit low overpotential in both alkaline and acidic media, and can even surpass commercial Pt / C at high current density in alkaline media, and can show excellent HER catalytic activity. In addition, they also have excellent hydrogen and electricity production capabilities.

[0047] 2. The present invention innovatively uses surface phosphating and calcination in a negative pressure hydrogen atmosphere, and further cooperates with the joint control of process parameters to successfully prepare the P-Se divacancy MoP / MoSe 2 Heterojunction materials, not only that, can also significantly improve the HER performance of the prepared materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 HER performance test diagram of the material prepared in Example 1 in 1M KOH. (a) Polarization curve (after iR compensation), (b) Tafel slope, (c) Nyquist curve and equivalent circuit diagram at a voltage of -0.07 V vs RHE, (d) at -10 mA cm -2 The chronopotentiometry curve lasted for 24 h.

[0049] Figure 2 The material prepared in Example 1 was heated to 0.5 MH 2 SO 4 HER performance test diagram. (a) Polarization curve (after iR compensation), (b) Tafel slope, (c) Nyquist curve and equivalent circuit diagram at a voltage of -0.16 V vs RHE, (d) at -10 mA cm -2 The chronopotentiometry curve lasted for 48 h.

[0050] Figure 3 The Zn-H assembled from the material prepared in Example 1 2 Schematic diagram, device diagram and battery performance diagram of O battery in 1M KOH. Among them, (a) MoP / MoSe 2 -H cathode and zinc plate anode constructed of Zn-H 2 O battery principle diagram; (b) MoP / MoSe 2 Zn-H as cathode 2 O battery device real picture; (c) MoP / MoSe 2 -Enlarged image of H cathode; (d) 3 MoP / MoSe 2 Zn-H as cathode 2 O cells in series to light up 12 LED lights; (e) Zn-H 2O battery polarization curve and corresponding power density curve; (f) MoP / MoSe 2 Zn-H as cathode 2 O cells at 1, 2, 3, 4, 5 mA cm -2 Constant current discharge curve under (g) MoP / MoSe 2 Zn-H as cathode 2 O cell at a current density of 3 mA cm -2 Long-term stability curve.

[0051] Figure 4 Schematic diagram of the synthesis route, XRD graph and EPR graph of the materials prepared in Example 1. 2 Schematic diagram of the synthesis route of -H, (b) MoSe 2 、MoP / MoSe 2 and MoP / MoSe 2 -H XRD pattern, (c) MoSe 2 (002) XRD magnified image, (d) MoP(101) XRD magnified image, (e) MoSe 2 、MoP / MoSe 2 and MoP / MoSe 2 -EPR diagram of H.

[0052] Figure 5 TEM images and selected area electron diffraction images of the material prepared in Example 1. 2 (e) MoP / MoSe 2 and (l)MoP / MoSe 2 -Low-resolution TEM images of H; (b, c) MoSe 2 、(fj)MoP / MoSe 2 and (m, n)MoP / MoSe 2 High-resolution (HR) TEM image of -H; (d) MoSe 2 (k) MoP / MoSe 2 and (p)MoP / MoSe 2 -H selected area electron diffraction (SAED) images; (o) corresponds to (n) MoP / MoSe 2 Diagram of the theoretical model of a heterojunction.

[0053] Figure 6 This is a high-angle dark field scanning transmission electron microscopy (HADDF-STEM) image of the material prepared in Example 1. 2 (a) MoP(001) crystal plane and (d) MoSe of -H sample2 HAADF-STEM image of the (002) crystal plane.

[0054] Figure 7 This is the XPS graph of the material prepared in Example 1, where (a) MoSe 2 、MoP / MoSe 2 and MoP / MoSe 2 -Full spectrum of H; MoSe 2 、MoP / MoSe 2 and MoP / MoSe 2 High-resolution spectra of (b) Mo 3d and (c) Se 3d of -H; MoP / MoSe 2 and MoP / MoSe 2 (d) High-resolution spectrum of P 2p of -H.

[0055] Figure 8 Polarization curves and Tafel slopes of the materials prepared in Example 3, where (a, b) are polarization curves and Tafel slopes in 1M KOH electrolyte; (c, d) are polarization curves and Tafel slopes in 0.5M KOH electrolyte. 2 SO 4 Polarization curves and Tafel slopes in electrolyte.

[0056] Fig. 9 Polarization curves and Tafel slopes of the materials prepared in Example 4, where (a, b) are polarization curves and Tafel slopes in 1M KOH electrolyte; (c, d) are polarization curves and Tafel slopes in 0.5M KOH electrolyte. 2 SO 4 Polarization curves and Tafel slopes in electrolyte.

[0057] Fig.10 Polarization curves and Tafel slopes of the materials prepared in Example 5, where (a, b) polarization curves and Tafel slopes in 1M KOH electrolyte; (c, d) 0.5M KOH electrolyte 2 SO 4 Polarization curves and Tafel slopes in electrolyte.

[0058] Fig.11 The polarization curves and Tafel slopes of the materials prepared in Comparative Example 1, where (a, b) are the polarization curves and Tafel slopes in 1M KOH electrolyte; (c, d) are the polarization curves and Tafel slopes in 0.5M KOH electrolyte. 2 SO 4 Polarization curves and Tafel slopes in electrolyte.

[0059] Fig.12The polarization curves and Tafel slopes of the materials prepared in Comparative Example 2, where (a, b) are the polarization curves and Tafel slopes in 1M KOH electrolyte; (c, d) are the polarization curves and Tafel slopes in 0.5M KOH electrolyte. 2 SO 4 Polarization curves and Tafel slopes in electrolyte.

[0060] Fig.13 The polarization curves and Tafel slopes of the materials prepared in Comparative Example 3, where (a, b) are the polarization curves and Tafel slopes in 1M KOH electrolyte; (c, d) are the polarization curves and Tafel slopes in 0.5M KOH electrolyte. 2 SO 4 Polarization curves and Tafel slopes in electrolyte.

[0061] Fig.14 The polarization curves and Tafel slopes of the materials prepared in Comparative Example 4, where (a, b) are the polarization curves and Tafel slopes in 1M KOH electrolyte; (c, d) are the polarization curves and Tafel slopes in 0.5M KOH electrolyte. 2 SO 4 Polarization curves and Tafel slopes in electrolyte. DETAILED DESCRIPTION

[0062] Table 1 shows the materials prepared in Example 2 in 1M KOH and 0.5M H 2 SO 4 η in the electrolyte 10 and Tafel slope Example 1

[0063] (1) Synthesis of MoSe on (carbon cloth) CC 2 CC (2×3 cm) was placed in acetone, ethanol, and deionized water for 20 min each, then nitrated, cleaned, and dried for later use. 0.316 g of selenium powder was dispersed in 10 mL of N 2 H 4 ·H 2 O and ultrasonically treated for 5 min to obtain a Se mixed solution. 4 ) 6 Mo 7 O 24 ·4H 2 O was dispersed in 30 mL of deionized water and ultrasonically treated for 5 min to obtain a Mo mixed solution. Then, the Mo mixed solution was added dropwise to the Se mixed solution during stirring to obtain a Mo / Se mixed solution. The pretreated CC and the Mo / Se mixed solution were transferred to a 70 mL polytetrafluoroethylene reactor and heated at 200 °C (hydrothermal temperature) for 12 hours to obtain the initial MoSe grown on the CC. 2 In order to match the MoSe with the P-Se divacancy-rich 2For comparison, the initial MoSe 2 MoSe was calcined at 800 °C in a high-purity argon (Ar) atmosphere at a heating rate of 10 °C / min for 1 hour and then cooled to obtain 2 .

[0064] (2) Synthesis of MoP / MoSe on CC 2 Heterojunction nanosheets: 2g NaH 2 PO 2 (P / MoSe 2 The molar ratio is 450:1) placed upstream of the quartz tube, and the MoSe 2 The (2×3 cm) was placed downstream of the quartz tube and heated to 800°C (marked as T1) at a heating rate of 10°C / min under Ar carrier gas (flow rate of 25 mL / min) and maintained for 1 hour for phosphating, and then cooled to room temperature to obtain MoP / MoSe 2 ; The flow rate of carrier gas is 25mL / min;

[0065] (3) Synthesis of MoP / MoSe rich in P-Se divacancy on CC 2 Heterojunction nanosheets: MoP / MoSe 2 The MoP / MoSe was kept in a vacuum state (pressure P is less than or equal to 250Pa) and heated to 800°C (marked as T2) at a rate of 10°C per minute and maintained for 1 hour. 2 Reduction is performed to produce P-Se divacancy, and the sample obtained after cooling to room temperature is MoP / MoSe. 2 -H.

[0066] In order to study the effects of heterostructure and P-Se divacancy on HER performance, we tested the HER performance of the catalyst in alkaline and acidic media. First, the polarization curve of the catalyst was tested in 1M KOH to determine its HER activity. Figure 1 As shown in a, MoP / MoSe 2 Heterostructured nanosheets only require an overpotential of 101 mV to achieve 10 mA cm -2 (10mA cm -2 Overpotential at: η 10 ) is significantly lower than that of MoSe 2 (212 mV), indicating that the heterostructure has a strong impact on the HER performance. 2 -H η 10 Value ratio MoP / MoSe 2The HER performance of MoP / MoSe catalyst in alkaline medium is improved. 2 -H overpotential in η 10 When the current density exceeds 70 mA cm -2 Even better than commercial Pt / C, such as Figure 1 In order to study the effect of heterogeneous structure and vacancies on the HER reaction kinetics, we calculated the Tafel slope, as shown in Figure 1 b. As expected, with MoSe 2 (142mV dec -1 ) and MoP / MoSe 2 (118mVdec -1 ) compared to MoP / MoSe 2 -H exhibited the fastest HER kinetic rate and had the smallest Tafel slope of 74 mVdec -1 , indicating that the P-Se divacancy synergistic heterostructure can significantly promote the HER catalytic kinetics.

[0067] In addition, we measured electrochemical impedance spectroscopy (EIS) to further compare the charge transfer capabilities of the catalysts. Figure 1 c shows that some semicircles are observed in the low-frequency region, indicating that the electrode process is kinetically controlled rather than mass transfer controlled. The equivalent circuit diagram is shown in the inset, where R s The constant phase element (CPE) represents the double layer capacitance under HER conditions due to the uncompensated series resistance, R CT (Z CT ) represents the charge transfer resistance in HER. Obviously, the semicircle radius can be ranked as follows: MoSe 2 >>MoP / MoSe 2 >MoP / MoSe 2 -H≈Pt / C, which is consistent with Figure 1 The trend of the overpotential shown in a is very consistent. The results show that MoSe 2 The heterogeneous interface between MoP and P-Se divacancy can significantly improve the charge transfer ability. In order to explore the practical application of the synthesized catalyst, its long-term stability was tested under constant current. Figure 1 As shown in d, at a current density of 10 mA cm -2 When MoP / MoSe 2 -H showed quite good stability within 24h.

[0068] The heterostructure-coupled P-Se divacancy had a positive effect on the HER activity in alkaline medium (1 M KOH). Similarly, the heterostructure-coupled P-Se divacancy also significantly improved the HER activity in acidic medium (0.5 M KOH). 2 SO 4 ) in the HER activity. 2 、MoP / MoSe 2 and MoP / MoSe 2 -H sequence, the overpotential gradually decreases from 255mV to 112mV ( Figure 2 a), Tafel slope decreased from 155 to 92 mV·dec -1 ( Figure 2 b). And MoP / MoSe 2 The semicircle diameter of the EIS of -H is only 8 ohms, which is much smaller than that of MoSe 2 and MoP / MoSe 2 EIS( Figure 2 c). In addition, MoP / MoSe 2 -H at 10mA cm -2 The test was conducted at a current density of 1.3 % and showed good stability within 48 h ( Figure 2 d) In conclusion, the heterostructure coupled P-Se divacancy makes MoP / MoSe 2 -H can exhibit excellent HER catalytic performance and stability in a wide pH range, and is expected to meet the different needs of the industry.

[0069] In order to expand the MoP / MoSe 2 -H heterostructure nanosheets, we use MoP / MoSe 2 -H as cathode and zinc sheet as anode to assemble into Zn-H 2 O battery, schematic diagram Figure 3 The actual device diagram is shown in a. Figure 3 As shown in b. Figure 3 It can be clearly seen in c that MoP / MoSe 2 After -H and zinc sheets form a closed loop, MoP / MoSe 2 A large amount of H is generated on the cathode surface 2 In addition, if Figure 3 As shown in d, three MoP / MoSe 2 -H as the cathode battery in series can light up 12 2V light-emitting diodes (LED). This phenomenon shows that the prepared Zn-H 2 O cells can produce hydrogen and electricity simultaneously. In addition, we tested the polarization curve and calculated the power density curve. Figure 3As shown in e, MoP / MoSe 2 Zn-H as cathode 2 O cells have the highest current density and the largest power density (120 mA cm -2 ,28.1mW cm -2 ), much higher than MoSe 2 As cathode (16.5 mA cm -2 ,2.9mW cm -2 )) and MoP / MoSe 2 As cathode (88 mA cm -2 ,22.3mW cm -2 ) of Zn-H 2 O battery. Obviously, MoP / MoSe 2 The battery with -H as cathode showed the best battery performance, which may be due to its excellent HER activity in 1 M KOH ( Figure 1 a). Figure 3 f shows the MoP / MoSe 2 Zn-H as cathode 2 O cells at 1, 2, 3, 4 and 5 mA cm -2 Constant current discharge curve under current density. Due to the consumption of dissolved oxygen, the initial voltage drops rapidly. After that, with the increase of discharge time and current density, the discharge platform of the battery continues to decrease slowly, which is attributed to the ZnO deposits generated on the anode surface. Long-term discharge stability is also an effective indicator for evaluating battery performance. Therefore, we tested MoP / MoSe 2 -H is the cathode of the battery at 3mAcm -2 The discharge curve of 125h discharge is as follows: Figure 3 As shown in g, the discharge platform only slightly decreases, showing excellent long-term stability. 2 Zn-H as cathode 2 O batteries not only have excellent discharge stability, but also have the ability to produce hydrogen and electricity simultaneously, and compared with other batteries, they do not require expensive diaphragms, which undoubtedly shows good development prospects.

[0070] MoP / MoSe enriched with P-Se divacancy 2 -H heterostructure nanosheets synthesis method such as Figure 4 a. First, MoSe was grown on CC by a simple hydrothermal reaction. 2 Nanosheets, then phosphated at high temperature to obtain MoP / MoSe 2 Heterostructured nanosheets were finally reduced by hydrogen at high temperature to obtain MoP / MoSe with rich P-Se divacancy. 2-H heterostructure nanosheets.

[0071] In order to explore MoP / MoSe 2 We have conducted a series of characterizations on the heterostructure and vacancies of -H. Figure 4 b shows pure hexagonal MoSe 2 (indicated by "◆", JCPDS no.17-0887) grown on CC (the diffraction peak at 26.2° belongs to CC). After phosphating, two diffraction peaks appeared: hexagonal MoSe 2 Indicated by “◆”, hexagonal MoP (JCPDS no.65-6487) The emergence of MoP indicates that MoP / MoSe 2 The heterostructure was successfully synthesized, and MoSe 2 The diffraction peaks of MoP and MoP / MoSe still exist 2 -H. After careful comparison and calculation, the results are as follows Figure 4 c and 4d, it can be clearly seen that MoSe 2 The FWHM of (002) increased from 0.8 to 0.83, and the FWHM of MoP(101) increased from 0.77 to 1.3. The results show that after hydrogen reduction, some defects (such as P vacancies and Se vacancies) formed, leading to the MoP / MoSe 2 -H in MoSe 2 and the crystallinity of MoP decreases. Accordingly, we use electron paramagnetic resonance (EPR) to monitor the changes in vacancy concentration. Figure 4 As shown in e, the EPR signal shows that pure MoSe 2 and MoP / MoSe 2 There are a certain number of vacancies. However, compared with MoP / MoSe 2 In contrast, hydrogen reduction leads to MoP / MoSe 2 -H EPR signal increased significantly, further proving that MoP / MoSe 2 More vacancies are formed in -H.

[0072] We further studied the specific structure of the synthesized samples by HR-TEM. Figure 5 a, e and l show MoSe 2 、MoP / MoSe 2 and MoP / MoSe 2 -H are all flower-like nanosheet structures. Figure 5 As shown in bd, MoSe 2 The high-resolution image and SAED image of MoSe show (002), (004), (101), (103), (105) and (110) crystal planes, which is consistent with the2 The XRD results of MoP / MoSe are very consistent. 2 ( Figure 5 fk) and MoP / MoSe 2 -H( Figure 5 m,n,p) HR-TEM shows the above-mentioned MoSe 2 In addition to the crystal planes of MoP, there are also (001), (100), (101) and (111) crystal planes. Figure 5 As shown in j, MoP / MoSe 2 Catalyst in MoSe 2 There is a clear heterogeneous interface between the (103) crystal plane and the adjacent MoP (101) crystal plane. Figure 5 MoP / MoSe 2 -H in MoSe 2 The heterogeneous interface between the (101) plane and the adjacent MoP (001) plane is also shown. Figure 5 o is consistent with the theoretical model. MoSe 2 The heterointerface between MoP and TiO2 can promote charge redistribution and form strong interactions, thus endowing the catalyst with high HER catalytic performance.

[0073] In order to directly observe the P-Se divacancy, we further used HAADF-STEM to observe the MoP / MoSe 2 -H electrocatalysts were characterized. Figure 6 As can be seen in a, the MoP(001) plane fully matches the theoretical model of MoP. Figure 6 There are a lot of P vacancies on the left side of a (marked by purple dotted circles). Figure 6 The P atom on the right side of a (marked with a brown solid circle) is still clearly visible. Figure 6 d, MoSe 2 There are also a large number of Se vacancies on the top of the (002) plane (marked by red dotted circles), while there are obvious Se atoms on the bottom (marked by orange solid circles). 2 -H structural analysis also shows the generation of P and Se vacancies, such as Figure 6 Therefore, the characterization results fully confirm the successful synthesis of MoP / MoSe rich in P-Se divacancy. 2 -H heterostructure nanosheets.

[0074] The X-ray photoelectron spectroscopy (XPS) analysis further investigated the relationship between MoP and MoSe. 2 The chemical states and interactions between Figure 7 As shown in a, MoSe 2 The XPS test results show the presence of Mo, Se, C and O elements, while MoP / MoSe 2 and MoP / MoSe 2 -H XPS test results show the presence of Mo, Se, P, C and O. Here, the C element mainly comes from the carbon cloth ground state, while the presence of O element is due to surface oxidation exposed to air, corresponding to Figure 7 Mo-O (~233.6 and ~236.75 eV) and PO (~134.1 eV) in b and 7d. 2 Mo 3d high-resolution spectrum ( Figure 7 b) There are two characteristic peaks at 229.44 and 232.57 eV, corresponding to MoSe 2 Mo 3d of Mo(+IV)-Se bond in 5 / 2 and Mo 3d 3 / 2 After phosphating, in addition to the above MoSe 2 In addition, two strong peaks appeared at ~228.8 and ~231.9 eV, corresponding to the Mo 3d 5 / 2 and Mo 3d 3 / 2 .

[0075] like Figure 7 c shows that compared with MoSe 2 The binding energy of Se 3d, MoP / MoSe 2 and MoP / MoSe 2 The binding energy of Se 3d of -H shows a significant negative shift (from 54.85 and 55.7 eV to 54.6 and 55.5 eV, respectively). The negative shift may be due to the stronger electronegativity of Se than P, resulting in the transfer of electrons from P to Se, indicating that MoSe 2 There is a strong interaction between MoP and MoP. More interestingly, compared with MoP / MoSe 2 , MoP / MoSe 2 The Se content of -H decreased significantly (from 7.8% to 6.3%), indicating that Se vacancies were formed after hydrogen reduction. Figure 7 d shows the P 2p of MoP 3 / 2 (~129.9 eV) and P 2p 1 / 2 (~130.7eV). Similar to the Se content, MoP / MoSe 2 -H has less P content (7.1%) than MoP / MoSe 2The P content of MoP / MoSe is 7.9%, indicating the formation of P vacancies. The formed P-Se divacancy can directly serve as an active site or induce unsaturated coordinated Mo as an active site for hydrogen evolution reaction. 2 -H ratio MoP / MoSe 2 It has higher HER catalytic activity.

[0076] Example 2

[0077] Compared with Example 1, the only difference is that in step (1), the hydrothermal temperature is changed to 180°C, 200°C (that is, Example 1), and 220°C. Other operations and parameters are the same as Example 1. The method of Example 1 is used to prepare the MoSe 2 Carry out η 10 , Tafel slope determination, the results are shown in Table 1:

[0078] Table 1 The materials prepared in this example were heated to 1M KOH and 0.5M H 2 SO 4 η in the electrolyte 10 and the Tafel slope Note:MoSe 2 -200 is the material prepared in Example 1.

[0079] Example 3

[0080] Compared with Example 1, the only difference is that the flow rate of the carrier gas in step 2 is changed. The argon carrier gas flow rates used in the phosphating process (step 2) are 0, 25 (Example 1) and 50 mL / min, respectively. The samples obtained in step 2 are recorded as MoP / MoSe 2 -A0、MoP / MoSe 2 -A25 (i.e., MoP / MoSe as described in Example 1) 2 ) and MoP / MoSe 2 -A50, the polarization curve and Tafel slope of the material are shown in Figure 8 Among them, (a, b) polarization curve and Tafel slope in 1M KOH electrolyte; (c, d) 0.5MH 2 SO 4 Polarization curves and Tafel slopes in electrolytes. Figure 8 It can be seen that MoP / MoSe has the best performance 2 -A25.

[0081] Example 4

[0082] Compared with Example 1, the only difference is that the heat treatment temperature of the T2 stage in step 3 is changed to 700, 800 (Example 1) and 900°C respectively. The samples obtained in step 3 are respectively recorded as MoP / MoSe 2 -H700, MoP / MoSe 2 -H800 (that is, MoP / MoSe as described in Example 1) 2 -H) and MoP / MoSe 2 -H900. Fig. 9 Polarization curves and Tafel slopes of the materials prepared in Example 4, where (a, b) are polarization curves and Tafel slopes in 1M KOH electrolyte; (c, d) are polarization curves and Tafel slopes in 0.5M KOH electrolyte. 2 SO 4 Polarization curve and Tafel slope in electrolyte. It can be seen that MoP / MoSe has the best performance. 2 -H800.

[0083] Example 5

[0084] Compared with Example 1, the only difference is that only the phosphating temperature of the T1 stage of step 2 is changed to 700, 800 (Example 1) and 900°C respectively. The samples obtained in step 2 are respectively recorded as MoP / MoSe 2 -700, MoP / MoSe 2 -800 (that is, MoP / MoSe as described in Example 1) 2 ) and MoP / MoSe 2 -900. Fig.10 Polarization curves and Tafel slopes of the materials prepared in Example 5, where (a, b) polarization curves and Tafel slopes in 1M KOH electrolyte; (c, d) 0.5M KOH electrolyte 2 SO 4 Polarization curve and Tafel slope in electrolyte. It can be seen that MoP / MoSe has the best performance. 2 -800.

[0085] Comparative Example 1

[0086] Compared with Example 1, the only difference is that the hydrogen reduction pressure in the heat treatment of stage T2 is different (step 3): vacuum (pressure less than or equal to 250 Pa) and normal pressure (pressure P is 1 atm). The products finally prepared in step 3 are marked as MoP / MoSe 2 -H vacuum (that is, MoP / MoSe as described in Example 1) 2 -H) and MoP / MoSe 2 -H normal pressure. Fig.11The polarization curves and Tafel slopes of the materials prepared in Comparative Example 1, where (a, b) are the polarization curves and Tafel slopes in 1M KOH electrolyte; (c, d) are the polarization curves and Tafel slopes in 0.5M KOH electrolyte. 2 SO 4 Polarization curves and Tafel slopes in electrolyte. Fig.11 The results show that MoP / MoSe 2 -H vacuum generates P-Se divacancy, MoP / MoSe 2 -H does not generate P-Se divacancy at normal pressure.

[0087] Comparative Example 2

[0088] Compared with Example 1, the only difference is that the phosphating temperature of step 2T1 is changed to 450 and 800°C respectively. The samples obtained in step 2 are respectively recorded as MoP / MoSe 2 -450 and MoP / MoSe 2 -800 (that is, MoP / MoSe as described in Example 1) 2 ). Fig.12 The polarization curves and Tafel slopes of the materials prepared in Comparative Example 2, where (a, b) are the polarization curves and Tafel slopes in 1M KOH electrolyte; (c, d) are the polarization curves and Tafel slopes in 0.5M KOH electrolyte. 2 SO 4 Polarization curves and Tafel slopes in electrolyte. Fig.12 The results show that MoP / MoSe 2 -450 No heterostructure is formed, and the HER performance is extremely poor; MoP / MoSe 2 -800 formed sufficient heterointerface and showed excellent HER performance.

[0089] Comparative Example 3

[0090] Compared with Example 1, the only difference is that in step (2), the carrier gas is 10% H 2 / Ar, and step (3) is omitted; that is, steps 2 and 3 are combined into one step. The obtained material is MoP / MoSe 2 -HP.

[0091] The results of Example 1 and Comparative Example 3 are shown in Fig.13 (MoP / MoSe in the figure 2 -AP-H is MoP / MoSe of Example 1 2 -H). This indicates that even when the argon inert gas was replaced with a hydrogen-argon reducing atmosphere in the step of synthesizing molybdenum phosphide, MoP / MoSe with P-Se divacancy could not be obtained. 2 Heterostructured nanosheets.

[0092] Comparative Example 4

[0093] Compared with Example 1, the only difference is that the amount of phosphorus source is changed, that is, the ratio of P to Mo is changed, which are 225:1, 450:1 (that is, Example 1) and 675:1 respectively. The samples obtained in step 2 are recorded as MoP / MoSe 2 -P225, MoP / MoSe 2 -P450 (i.e., MoP / MoSe as described in Example 1) 2 ) and MoP / MoSe 2 -P675.

[0094] The results show that MoP / MoSe 2 -P225 and MoP / MoSe 2 -HER performance of P675 ( Fig.13 b, d) with MoSe 2 The HER performance of MoP / MoSe is similar. 2 -P225 does not form sufficient heterointerface, while MoP / MoSe 2 -P675 almost completely generates MoP without forming a heterostructure, so MoP / MoSe 2 -P225 and MoP / MoSe 2 -The HER performance of P675 has not been improved.

Claims

1. A method for preparing a P-Se divacancy MoP / MoSe2 heterojunction material, characterized in that: MoSe2 nanosheets are prepared, and then surface phosphating is performed in a phosphorus source atmosphere to obtain a MoP / MoSe2 heterojunction material; wherein the molar ratio of P in the phosphorus source to the MoSe2 nanosheets is 300-500:1, and the phosphating temperature is 700-900°C; The MoP / MoSe2 heterojunction material is calcined in a reducing atmosphere and under negative pressure to obtain the P-Se divacancy MoP / MoSe2 heterojunction material; wherein the calcination temperature is 700-900° C., and the negative pressure during the calcination stage is less than or equal to 250 Pa; The P-Se double vacancy MoP / MoSe2 heterojunction material comprises a MoSe2 nanosheet with Se vacancies and a MoP nanosheet with P vacancies composited on the surface thereof, and the composite interface of the two has a heterojunction structure.

2. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 1, characterized in that: The P-Se divacancy MoP / MoSe2 heterojunction material has a flower-like nanosheet structure.

3. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 1, characterized in that: The molybdenum source and the selenium source are subjected to a hydrothermal reaction to obtain the MoSe2 nanosheets.

4. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 1, characterized in that: The modified carbon cloth, molybdenum source and selenium source are subjected to a hydrothermal reaction to obtain the MoSe2 nanosheets.

5. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 4, characterized in that: The modified carbon cloth is nitrated carbon cloth.

6. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 3, 4 or 5, characterized in that: Molybdenum sources include ammonium molybdate.

7. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 3, 4 or 5, characterized in that: The selenium source is at least one of elemental selenium and selenate.

8. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 3 or 4, characterized in that: The temperature of the hydrothermal reaction is 150~250℃.

9. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 1, characterized in that: The phosphorus source is PH3 or a precursor that can be converted into PH3.

10. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 9, characterized in that: The precursor is at least one of sodium hypophosphite, potassium hypophosphite and red phosphorus.

11. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 1, characterized in that: In the surface phosphating stage, the precursor is placed upstream of the gas source, and the MoSe2 nanosheets are placed downstream of the gas source. The phosphorus source is heated and volatilized under the carrier gas, and the surface of the MoSe2 nanosheets is phosphated under the action of the carrier gas.

12. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 11, characterized in that: The temperature in the phosphating stage is 750~850℃.

13. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 11, characterized in that: The carrier gas is at least one of inert gases.

14. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 11, characterized in that: The flow rate of the carrier gas during the phosphating treatment stage is less than or equal to 50 mL / min.

15. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 11, characterized in that: The flow rate of the carrier gas during the phosphating treatment stage is 10~30mL / min.

16. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 11, characterized in that: The flow rate of the carrier gas during the phosphating treatment stage is 15~25mL / min.

17. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 11, characterized in that: The phosphating treatment time is 0.5~1.5h.

18. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 1, characterized in that: During the calcination process, the reducing atmosphere is a hydrogen-containing atmosphere.

19. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 18, characterized in that: The reducing atmosphere is at least one of hydrogen, a hydrogen-nitrogen mixed gas, and a hydrogen-inert gas mixed gas.

20. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 18 or 19, characterized in that: In the reducing atmosphere, the volume content of hydrogen is greater than or equal to 1v%.

21. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 18 or 19, characterized in that: In the reducing atmosphere, the volume content of hydrogen is 10-100v%.

22. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 1, characterized in that: The temperature in the calcination stage is 750~850℃.

23. The method for preparing the P-Se divacancy MoP / MoSe2 heterojunction material according to claim 1, characterized in that: The holding time at the calcination temperature is 0.5 to 5 hours.

24. An application of a P-Se divacancy MoP / MoSe2 heterojunction material prepared by the preparation method according to any one of claims 1 to 23, characterized in that: It is used as a HER catalyst.

25. The use according to claim 24, characterized in that It can be used as a HER catalyst for water electrolysis to produce hydrogen and / or batteries.

26. The use according to claim 25, characterized in that The battery is a Zn-H2O battery.

27. The use according to claim 25, characterized in that The battery is a diaphragm-free Zn-H2O battery.

28. A HER catalytic electrode, characterized in that A P-Se divacancy MoP / MoSe2 heterojunction material prepared by the preparation method according to any one of claims 1 to 23.

29. A device comprising the HER catalytic electrode according to claim 28, characterized in that: It is a device and / or battery for producing hydrogen by electrolyzing water.

30. The HER catalytic electrode device according to claim 29, characterized in that: The battery is a Zn-H2O battery.

31. The HER catalytic electrode device according to claim 29, characterized in that: The battery is a diaphragm-free Zn-H2O battery.

Citation Information

Cited By

  • MoP-coated Ni-LDH heterojunction nano-material for efficient electro-catalytic hydrogen production and preparation method of MoP-coated Ni-LDH heterojunction nano-material

    CN121931554A